Approaches to the Analysis of Metadiscourse Features in Political Discourse - Albalat-Mascarell, Ana (Complutense Journal of English Studies, 2023)
Metadiscourse features play a decisive role in the attainment of persuasion in different discourse domains and genres. Political genres, generally linked to the formal expression of viewpoints by national and international leaders, displays a vast amount of metadiscourse features aimed at persuading large audiences. This article offers a critical review of some important approaches to the study of metadiscourse traits in political discourse. The paper is organized as follows: (1) an introduction to the concept of metadiscourse and its potential as an analytical framework for the study of persuasion; (2) a description of contemporary political discourse, highlighting some current characteristics of political genres; (3) a discussion of the main approaches to the examination of political genres from a metadiscoursal perspective; and (4) conclusions on the strengths and shortcomings of the abovementioned approaches as regards the exploration of persuasive aspects in contemporary political talk.